2020
DOI: 10.21203/rs.2.21075/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indoor air pollution concentrations and cardiometabolic health across four diverse settings in Peru: a cross-sectional study

Abstract: Background: Indoor air pollution is an important risk factor for health in low- and middle-income countries. Methods: We measured indoor fine particulate matter (PM 2.5 ) and carbon monoxide (CO) concentrations in 617 houses across four settings with varying urbanisation, altitude, and biomass cookstove use in Peru, between 2010 and 2016. We assessed the associations between indoor pollutant concentrations and blood pressure (BP), exhaled carbon monoxide (eCO), C-reactive protein (CRP), and haemoglobin A1c (Hb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although some studies have found positive associations between HAP and CRP, 54,56 others have also found null associations 57,74,75 . Two previous studies in Puno did not identify CRP associations with biomass stove users 53,76 . However, lifestyle differences (ie, more physical activity among rural participants who primarily worked as farmers) may have contributed to the lower concentrations of CRP observed among rural participants 53 .…”
Section: Discussionmentioning
confidence: 96%
“…Although some studies have found positive associations between HAP and CRP, 54,56 others have also found null associations 57,74,75 . Two previous studies in Puno did not identify CRP associations with biomass stove users 53,76 . However, lifestyle differences (ie, more physical activity among rural participants who primarily worked as farmers) may have contributed to the lower concentrations of CRP observed among rural participants 53 .…”
Section: Discussionmentioning
confidence: 96%
“…It is also possible that the observed BP elevation in the intervention group, observed in the ITT analysis, was attributable to exposures to other unmeasured pollutants from using the LPG stove, such as nitrogen dioxide, 43 polycyclic aromatic hydrocarbons, 44 and volatile organic compounds. 45 More comprehensive personal HAP exposure characterization is needed to fully understand the effect of specific HAP constituents on BP.…”
Section: Discussionmentioning
confidence: 99%